MULTI-COMPONENT VARIABILITY OF THE SYNCHRONIZING POLAR BY CAM - Andronov, I. L.; Antoniuk, K. A.; Breus, V. V.; Chinarova, L. L.; Han, W.; Jeon, Y. -B.; Yonggi, Kim; Kolesnikov, S. V.; -Y, Oh. J.; Pavlenko, E. P.; Shakhovskoy, N. M. (Одеські астрономічні публікації, 2007)
---